PERAN PEMERINTAH DAERAH DAN SWASTA DALAM PENGELOLAAN DAN PENGEMBANGAN PASOLA SEBAGAI OBJEK PARIWISATA, DI KECAMATAN WANUKAKA, KABUPATEN SUMBA BARAT, PROVINSI NUSA TENGGARA TIMUR - Wolu Ate, Elton Laiya; Kebayantini, Ni Luh Nyoman; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT Pasola which means a kind of wooden spear the ends blunt used to throw over the top horses.The issues examined in this study ar, the role of local governments and the private sector in the management and development of tourism objects as pasola, socio-economic impacts of the pasola for society life. The purpose of this research is to address these problems by using qualitative research methods.The theory is the theory of community empowerment of Norman Uphoff. Based on the results of this study show that in the management and development of the pasola is no role local governments and private parties so that through some analysis of the principles of empowerment, local communities can be empowered and independent own .So the existence of the role of local authorities and private parties in the management and development of the pasola gives a positive economic impact for the community Wanukaka. Keywords: Pasola, the role of local authorities and private parties, community Empowerment